Methodological Quality of Physical Therapy Guidelines and Their Suitability for Adaptation: A Scoping Review. Issue 8 (21st April 2020) - Becker, Monika; Strunk, Katharina; Buschhaus, Niels; Bühn, Stefanie; Pieper, Dawid
Abstract: Objective: Clinical practice guidelines (CPGs) can be characterized to the extent that they specifically address physical therapists and mainly contain recommendations for physical therapist interventions. The primary aim of this study was to identify existing physical therapy CPGs regardless of medical condition, with a secondary aim of assessing their methodological quality to determine whether they are potentially suitable for adaptation. Methods: Systematic searches of the Medline and Physiotherapy Evidence Database were performed (August 2019), and the websites of World Confederation for Physical Therapy members were screened (September 2019). Only CPGs published in German or English were included. Two independent reviewers screened records according to previously defined inclusion criteria. Information was extracted regarding country of origin, year of publication, and clinical subject area addressed. Four independent reviewers assessed the quality of physical therapy CPGs using the Appraisal of Guidelines Research and Evaluation instrument. A descriptive data analysis was performed. Results: Thirty-five CPGs met the inclusion criteria; 46% (16/35) of the included CPGs were from the United States, and 31% (11/35) were from the Netherlands. Assessment using the Appraisal of Guidelines Research and Evaluation tool resulted in the following domain scores, presented as median percentage (interquartile range): domain 1 (scope and purpose), 76 (63–92); domain 2 (stakeholder involvement), 63 (55–76); domain 3 (rigor of development), 67 (53–75); domain 4 (clarity of presentation), 74 (67–77); domain 5 (applicability), 44 (30–57); and domain 6 (editorial independence), 52 (35–66). Conclusions: In general, the methodological quality of the included CPGs was moderate to good. Possibilities of adapting recommendations from existing CPGs should be considered with the development of new physical therapy CPGs. Impact Statement: This study can raise awareness of existing physical therapy CPGs and can support their application by physical therapists. Further, the study can support decisions on adapting existing CPGs with the planning of new physical therapy CPGs.